PENGARUH BUDAYA ORGANISASI, PELATIHAN, DAN KOMITMEN TERHADAP KINERJA KARYAWAN(STUDI KASUS PT MARKAINDO SELARAS SENTUL) - Dinda Saputri (2022)
This research involving 36 employees was conducted to find out whether organizational culture, training, and commitment to employee performance affect employee performance. PT Markaindo Selaras became the research subject. The information used in this study was obtained from a survey distributed via the Google form. SmartPLS 3.0 software is used to perform partial tests (T test) and simultaneous tests (F test). (1) There is a positive and significant influence of organizational culture on the performance of employees of PT Markaindo Selaras according to the research results. (2) At PT Markaindo Selaras, training has a positive and significant impact on employee performance. (3) Commitment has a positive and significant effect on the performance of employees of PT Markaindo Selaras. (4) At PT Markaindo Selaras, organizational culture, training, and commitment to employee performance impact simultaneously.